Using Artificial Intelligence in the Field of Disabilites: Benefits, Risks, and Challenges - Dr. Rouaida Mohammed Ad Abpzaid; Dr. Khalifa Ab Khalifa Nusrat (Journal of Scientific and Human Dimensions, 2026)
In recent years, there has been rapid development in the field of artificial intelligence, making it an effective tool in education, especially for individuals with special needs. These individuals face multiple challenges that require innovative solutions to improve their quality of life, with AI applications being prominent in enhancing personalized learning and interaction, while ensuring fairness and privacy. The study aims to explore the benefits, risks, and challenges associated with using artificial intelligence in education for people with special needs, and to identify its areas of application and fairness standards in its use. The researchers adopted a descriptive survey and analytical approach by reviewing previous studies, in addition to a questionnaire directed at teachers and parents, and analyzed the data using SPSS software. The results showed that artificial intelligence enhances the quality of education and provides opportunities for personalized learning, but it requires careful management of privacy risks and overreliance on technology. The study recommended applying fairness standards in designing and using AI systems, adopting smart educational applications that support the empowerment of individuals with special needs, and facilitating their integration into society.